2013
DOI: 10.4161/auto.23839
|View full text |Cite
|
Sign up to set email alerts
|

A chimerical phagocytosis model reveals the recruitment by Sertoli cells of autophagy for the degradation of ingested illegitimate substrates

Abstract: Phagocytosis and autophagy are typically dedicated to degradation of substrates of extrinsic and intrinsic origins respectively. Although overlaps between phagocytosis and autophagy were reported, the use of autophagy for ingested substrate degradation by nonprofessional phagocytes has not been described. Blood-separated tissues use their tissue-specific nonprofessional phagocytes for homeostatic phagocytosis. In the testis, Sertoli cells phagocytose spermatid residual bodies produced during germ cell differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 65 publications
0
49
0
Order By: Relevance
“…54,55 They therefore could not present the exogenous constriction force, and so the precise function remains controversial. 13 Autophagy is active in Sertoli cells, [26][27][28][29] and early morphology studies found that the lysosomes of the seminiferous epithelium show cyclical variations. Chemes speculates that germ cell residual body disposal might be initiated by autophagy and completed by Sertoli cell phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54,55 They therefore could not present the exogenous constriction force, and so the precise function remains controversial. 13 Autophagy is active in Sertoli cells, [26][27][28][29] and early morphology studies found that the lysosomes of the seminiferous epithelium show cyclical variations. Chemes speculates that germ cell residual body disposal might be initiated by autophagy and completed by Sertoli cell phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…20 Autophagy participates in cell growth, adaptation to stress conditions, anti-aging mechanisms, intracellular quality control, renovation during development and differentiation and the biogenesis of organelles such as cilia and acrosome. 21,[23][24][25] Autophagy is also active in Sertoli cells, [26][27][28][29] where it is involved in the clearance of SHBG/ABP that is selectively regulated by testosterone. 26 However, the role of autophagy in Sertoli cells is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that autophagy plays a regulatory role in spermatogenesis impairment targeting the injurious biochemical and molecular cascade (Wang et al 2014b;Yefimova et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, autophagy is selectively involved in the degradation of those illegitimate substrates in Sertoli cells, and the inhibition of autophagy significantly retarded the degradation of illegitimate substrates [47].…”
Section: Autophagy Is Required For Structural Modulation In Sertoli Cellmentioning
confidence: 99%
“…In Sertoli cells, both autophagy and phagocytosis may undertake similar mission under certain circumstance, especially once a phagocytic vesicle has entered a cell. Numerous evidences had suggested that autophagy is associated with the process of phagocytosis and is atypically implicated in the degradation of external substrates entering via phagocytosis in Sertoli cells [47]. Generally, blood-separated tissues use their tissue specific nonprofessional phagocytes for homeostatic phagocytosis [48].…”
Section: Autophagy Is Required For Structural Modulation In Sertoli Cellmentioning
confidence: 99%